1982
DOI: 10.2172/5259641
|View full text |Cite
|
Sign up to set email alerts
|

Alfven wave. DOE Critical Review Series

Abstract: Books published by the Center include undergraduate, graduate, and workshop textbooks; handbooks and manuals; reference books; monographs; specialized reviews; and DOE-sponsored symposium, workshop, and short-course proceedings. FOR E w ORD This publication is the second in the Advances in Fusion Science and Engineering series, a part of the DOE Critical Review Series. The purpose of the Advances in Fusion Science and Engineering series is to provide the fusion research community with high-quality reviews in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 17 publications
1
47
0
Order By: Relevance
“…When a fast electron beam with a thin density (n b n 0 ) and fast velocity (v b v A ) along the ambient magnetic field is present in a magnetized plasma, it carries a field-aligned electric current j b = −en b v b passing through the plasma, where n 0 is the ambient plasma density and v A the Alfvén velocity. This current may cause magnetic fluctuations via the Alfvén waves (AW) instability in the low-frequency (ω ω ci ) and long-wavelength (k ω ci /v T i ) limit (Hasegawa 1975;Hasegawa & Uberoi 1982;Wu 2012), where ω and k are the frequency and wavenumber of AWs, respectively, and ω ci and v T i the ion gyrofrequency and thermal speed, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…When a fast electron beam with a thin density (n b n 0 ) and fast velocity (v b v A ) along the ambient magnetic field is present in a magnetized plasma, it carries a field-aligned electric current j b = −en b v b passing through the plasma, where n 0 is the ambient plasma density and v A the Alfvén velocity. This current may cause magnetic fluctuations via the Alfvén waves (AW) instability in the low-frequency (ω ω ci ) and long-wavelength (k ω ci /v T i ) limit (Hasegawa 1975;Hasegawa & Uberoi 1982;Wu 2012), where ω and k are the frequency and wavenumber of AWs, respectively, and ω ci and v T i the ion gyrofrequency and thermal speed, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Solitary kinetic Alfvén waves (SKAWs) arise when the dispersion relation of ordinary Alfvén waves is modified by the finite Larmor radius effect or simply by the finite electron inertial effect [1]. Recent data from the Freja satellite [2,3] showed that the auroral low-frequency turbulence is dominated by strong electromagnetic spikes, which resemble solitary structures and can be interpreted as SKAWs.…”
Section: Introductionmentioning
confidence: 99%
“…As is known (e.g. Hasegawa and Uberoi, 1982;Voitenko and Goossens, 2004), this contribution for Alfvén waves ω ω i and N 2 1 is the following: ω = k z c A 1 + k 2 ⊥ ρ 2 s 1/2 , where ρ s is the ion acoustic gyroradius and k ⊥ is the wave number across the background magnetic field. In the case k 2 ⊥ ρ 2 s 1 which is here considered, this term can be neglected in our calculations for the real value N 2 1.…”
Section: Ponderomotive Forcementioning
confidence: 99%